Three-level universal electric vehicle charger based on voltage-oriented control and sinusoidal pulse-width modulation - Al-Ogaili, Ali Saadon Mtair (2017)
The electric vehicle (EV) could be one of the solutions to address the issues of the environmental pollution and the depletion problems of non-renewable energy resources. EVs, which are energized by a battery storage system, are becoming attractive because it keeps the environment clean and friendly. The battery charger of EV needs to have a sufficient performance by a unity power factor and zero harmonic distortion. This work presents the design process of a universal EV charger. The proposed charger is able to provide a controllable and constant charging voltage for a variety of EVs. It is composed of three levels of charging: (1) 650 V/100 A DC for bus or lorry, (2) single-phase 120 V/16 A AC for motorcycle, and (3) three-phase 240 V/60 A for saloon car battery charging. The power system of this work consists of two converters: (1) the three-phase pulse-width modulated (PWM) of a bridge rectifier with an output of 650 V DC unregulated voltage, and (2) the converter is for the three-phase DC–DC converter. To satisfy the voltage control and the isolation between Grid To Vehicle (G2V), a three-phase transformer has been exploited within the DC–DC converter. The primary output circuit achieved the charge Levels 1 and 2, while the whole circuit output can charge Level 3 or the DC charge. For efficient and secure battery charging, voltage-oriented control (VOC) technique is proposed.A study is conducted to investigate the use of a three-phase converter unidirectional EV battery charger. In the proposed design, the reactive and unstable active currents can be counteracted by the PWM rectifier via the input and output filters and PFC. The current controller and DC‐link voltage controller have been designed using a technique called internal model control. The unity power factor for the PWM-based rectifier and SPWM are designed and evaluated using MATLAB/Simulink 2010a block sets. The total harmonic distortion (THD) for the input current is recorded as less than 0.85 %. A prototype and simulation results are used to validate the proposed EV charger to ensure its robustness, accuracy, and application.